Implementation Of An-Nubuwwah Values In Marketing Strategies To Increase Consumer Buying Interest (Case Study Of Arafah Cake Shop In Gowa Regency) - Rahmaniar; Jamaluddin Majid; Mustakim Muchlis (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This research aims to analyze and examine (1) the implementation of An-Nubuwwah (prophetic) values in the marketing strategy of Arafah Cake Shop to increase consumer buying interest, and (2) the impact of implementing An-Nubuwwah values on consumer buying interest. JThe type of research used is descriptive qualitative.This research is a field study and does not use statistical data. Data were obtained directly from the field through observation, in-depth interviews (with the store owner, two employees, and two loyal customers), and document analysis. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, with data validity tested using source and technique triangulation techniques.The application of An-Nubuwwah values (Shiddiq, Amanah, Tablīgh, Faṭonah) in the marketing strategy of Arafah Cake Shop has a significant positive impact on consumer buying interestThis value has successfully built a solid "Trust Capital," where trust driven by consistent product quality (Shiddiq) and fair pricing (Amanah) serves as a Unique Selling Proposition (USP). Consequently, the store achieves long-term loyalty and consistent, ethical repeat purchases. Theoretically, this study shows that the values of An-Nubuwwah (especially Shiddiq and Amanah) are key predictive factors that shape long-term customer loyalty, beyond conventional discount strategies.Practically, business actors (MSMEs) are advised to focus on internalizing ethics and moral consistency to build "Trust Capital," as this has been proven effective in creating sustainable, morally-based competitive advantages.